OPTIMASI PENDISTRIBUSIAN PRODUK MENGGUNAKAN MODEL FUZZY MULTIOBJEKTIF CYCLICAL INVENTORY ROUTING PROBLEM - SUSANTI, EKA; INDRAWATI, INDRAWATI; SITEPU, ROBINSON; NABILA, ANNISA; WULANDARI, RISKA (E-Jurnal Matematika; Vol 9 No 1 (2020)DO - 10.24843/MTK.2020.v09.i01.p285, 2020)
In distribution activities, travel time is influenced by several factors, such as vehicle conditions, traffic conditions and road conditions. Uncertain traffic conditions cause the travel time can not be defined with certainty (uncertain). If several variables are in a uncertain condition then a deterministic approach is not appropriate. Fuzzy approach, can be used to overcome uncertainty conditions. In this study, the optimal route for chicken egg delivery using the fuzzy Multiobjective Cyclical Inventory Routing Problem (FMOCIRP) model with time and cost is expressed by triangular fuzzy numbers. Model completion using Winqsb software. An optimal shipping route is obtained with a total cost of Rp 114,000 and a total delivery time of 132 minutes. The first optimal delivery route is distributor, retailer 1, retailer 2, retailer 3 and back to the distributor. The second route is distributor, retailer 5, retailer 4 and back to the distributor.